(untitled) (Revista de História Regional, 2007)
The project did not aim any action towards one specific community, but to safeguard, through technical procedures, the documents produced by the Congregação do Verbo Divino since it came to Ponta Grossa, in 1903, to the present. Besides the internal documents, the collection is composed of newspapers and other periodical collections, books, pamphlets, reports, minutiae and annals of national meetings, catalogs, photographies, etc. The large amount of material was kept by Seminário Verbo Divino, which was a provisory headquarter for the SVD and, so, centralized the archives foo all the written materials regarding the congregation. The project allows History students to put into practice the theoretical knowledge acquired in the respective undergraduate disciplines dealing with archives, museums and historical heritage.